Protein Synthesis by Bradyrhizobium japonicum Bacteroids Declines as a Function of Nodule Age - Karr, D. B. (1996)
Isolated bacteroids of Bradyrhizobium japonicum accumulated exogenously supplied [(sup35)S]methionine or [(sup3)H]leucine and incorporated them into cytosolic proteins. The accumulation of these labeled amino acids was inhibited by azide. Only 3 to 6% of these accumulated amino acids were incorporated into protein. Protein synthesis was not stimulated by incubation of bacteroids in the presence of potassium salts, malate, or amino acids, but azide, chloramphenicol, and acridine did inhibit the process. No prominent differences were observed in autoradiograms after sodium dodecyl sulfate-polyacrylamide gel electrophoresis of (sup35)S-labeled bacteroid proteins as a function of nodule age. The rates of protein synthesis and protein turnover declined during nodule development. Protein synthesis declined about 60% between 14 and 20 days after planting, which is the period of a rapid increase in acetylene reduction activity. This correlation suggests a metabolic mechanism by which significant amounts of cellular energy are diverted to the nitrogen fixation process.